South Pacific - Hammerstein, Oscar 1895-1960.; Rodgers, Richard 1902-1979; Gaynor, Mitzi 1930-.; Brazzi, Rossano 1916-.; Logan, Joshua; Adler, Buddy 1906-1960. ([S.l.] CBS-Fox Video distributed by the Samuel Goldwyn Co.)
Romance on the South Seas set against the backdrop of a world at war.
VHS.
Includes South Pacific overture and trailers.
Adapted from the play "South Pacific" by Richard Rodgers, Oscar Hammerstein II and Joshua Logan.
Based on "Tales of the South Pacific" by James A. Michener.
originally produced on the stage by Richard Rodgers, Oscar Hammerstein II, Leland Hayward and Joshua Logan.
Originally produced on the stage by Richard Rodgers, Oscar Hammerstein II, Leland Hayward and Joshua Logan.
Keywords: Feature films; Musical films